Lucio Phenomenon: A Rare Manifestation of Leprosy in Selangor, Malaysia - Binti Allapitchai, Shahrizan Majid (International Journal of Human and Health Sciences (IJHHS), 2021)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae, predominantly affecting the skin and peripheral nerves. Lucio phenomenon is a rare reactional state presenting in patient with lepromatous leprosy and described as acute cutaneous necrotising vasculitis. We discussed the case of a 38-year-old male patient presenting with oedematous and dusky discolouration of bilateral hands and feet associated with diffuse facial involvement. His skin condition gradually worsened to form multiple ulcers with bizarre shaped purpuric lesion over bilateral upper and lower limbs, trunk, and face. Histopathological examination of the skin biopsy showed multiple acid-fast bacilli and diagnosis of Lucio’s phenomenon was made in the background of lepromatous leprosy. He was treated with multi drug therapy (MDT) as recommended by the WHO guidelines. A better understanding of rarer manifestation of this illness is important for early diagnosis and to prevent significant morbidity associated with it. International Journal of Human and Health Sciences Supplementary Issue-2: 2021 Page: S20